[quotation] 'The integration of the rural world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'The integration of the rural world into the urban world is irreversible' from Views from the South, IRAM/Harmattan, 1998